DOES CSR EXPENDITURE REWARD THE FINANCIAL PERFORMANCE OF NIGERIAN QUOTED OIL AND GAS COMPANIES: A POOLED PANEL REGRESSION MODEL? - Abdulsalam, Tajudeen Alaburo; OGUNGBEMI, Samuel Seun; Tajudeen, Rofiat Bolanle (Ekonomski pogledi, 2024)
Nigeria's oil and gas industry has significantly harmed the environment, with a 5 to 10 percent loss of mangrove ecosystems and the deforestation of 8,400 km² of rainforest. The industry has been criticized for prioritizing profits over social and environmental responsibilities. The research examines how CSR expenditure affects the financial performance of Nigeria's oil and gas sector. By utilizing a positivist approach guided by quantitative methodology, the study analyses panel data from the annual and sustainability reports of listed oil and gas companies from 2013 to 2023, using pooled least squares panel regression. The findings reveal that CSR initiatives, such as donations, educational programs, and empowerment projects, positively influence financial metrics like return on assets, return on equity, net assets, and net profit margin. Consequently, the study concludes that CSR expenditures significantly enhance the overall financial performance of these companies, despite social and regulatory challenges hindering their global growth. The research suggests improving measurement and reporting systems, engaging local communities in CSR projects, and developing communication strategies to highlight CSR achievements. While the study makes substantial contributions to academic literature in theory, research, and management, it acknowledges a potential bias due to its reliance on annual and sustainability reports, suggesting the need to explore additional industry, region, and data sources.
Keywords: Corporate Social Responsibility (CSR); Environmental Impact; Financial Performance; Oil and Gas Industry; Sustainability Reporting